Analyzing contribution of pioneeringteachers to improv their competence in Rote Ndao district in East Nusa Tenggara - Fembriani, Fembriani; Rahman, Abdul; Karsidi, Ravik; Koroh, Taty R; Nawa, Netty E A; Koehua, Viola (Universitas Nusantara PGRI Kediri, 2024)
Pioneering teacher is a new breakthrough to improve teacher competence. Teacher competencies are more sharply will result in a better quality of education. The purpose of this study was to see the benefits and contributions of pioneering teachers in improving their competence as a teacher in Rote Ndao district. This study used a qualitative descriptive approach through questionnaires and interviews with 6 Pioneering teachers in Rote Ndao district. Based on the results of research that after participating in the pioneering ing teacher program, the four teacher competencies increased, this is evidenced by the personality competence pioneering teachers of Rote Ndao being able to show a better personality by displaying an independent nature and willing to share knowledge with fellow teachers at school. The pedagogic competence of pioneering teachers is able to provide learning materials that are more applicable to students and apply literacy in schools. The social competence of Rote Ndao Pioneering teachers has been able to engage in society more existently and consistently and the professional competence of pioneering teachers proves that they are always professionals with high discipline. Thus, pioneering teacher program has made a positive contribution in Rote Ndao district, East Nusa Tenggara